(untitled) (International Journal of Built Environment and Sustainability, 2016)
This paper presents the concept of ecosystem services and its trend, scale and gradient, through reviewing articles, books and internet sources. Result shows that evaluation of ecosystem services in small towns within urban-rural gradient in developing countries still not being scrutinized explicitly, especially trade-offs’ concern. Environmental damages in the developing countries are burgeoning. As land conversion from natural capital to built capital is also keep on rising for temporal economic interests. Therefore, it has induced changes in ecological functions and affected the ecosystem services supply. In the context of Peninsular Malaysia, ungoverned built capitals and flaw of policy further contribute to fallacious decision making. And yet, there is still no specific framework or initiatives directly deals with ecosystem and biodiversity. A conceptual framework has been proposed to assess and value ecosystem services through integration of InVEST model (Integrated Valuation of Ecosystem Services and Tradeoffs) and bundle of ecosystem services. The framework allows stakeholders to have an insight of the pros and cons about the landscape changes, be it in ecological, economic or social-cultural perspectives. Therefore, it may help to ameliorate the trade-offs and enhance the synergies of ecosystem services that eventually can contribute to attaining human well-being, and to promote sustainable growth.